Teknik Distraksi Mendengar Murottal Al-Qur’an Terhadap Penurunan Intensitas Nyeri Pada Pasien Pascaoperatif - Mira Astry Koniyo; Rahmawati Mansur; Rahmawati I Tolinggi (Poltekkes Kemenkes Gorontalo, 2021)
Background: Surgery is defined as the medical diagnosis and treatment of injuries, disabilities, and diseases through manual and instrumental operations. Surgery can result in injury to the patient's body, so that pain or discomfort can arise, this usually occurs in the postoperative stage. Pain control measures (murottal Al-Qur'an listening distraction technique) are used to support the pharmacological therapy that has been given.Objective: to analyze the effect of the distraction technique of listening to murottal Al-Qur'an on reducing pain intensity in postoperative patients.Methods: This study uses a Pre Experimetal type of research with One-Group Pretest-Posttest Design.Results: The results of the research and analysis using the paired t statistical test found that the t table with a significance degree of : 0.05 is 2.93 and the t count is 8.236 which is greater than the t table. The average value of the respondent's pain scale before treatment was 5.40 ± 1.095 while the average value of the respondent's pain scale after treatment was 3.35 ± 1.596.Conclusion: there is a significant effect of distraction technique listening to murottal Al-Qur'an on decreasing pain intensity in postoperative patients.